Networked Communication and the Collaborative Development of Written Expression at Key Stage Three - Walker, S. Aisha; Pilkington, Rachel M. (Proceedings of the International Conference on Networked Learning, 2000)
In Britain's inner cities, there are many children with a 'literacy deficit• whose educational potential may not be fulfilled because they lack skills for communication through written language. Previous research suggests that computer-mediated communication (CMC) may encourage the development of literacy skills by increasing motivation and enhancing inclusive participation in text-based discussion. A study was carried out to explore the effect of text-based CMC on the literacy skills of a group of key-stage three children. The results showed improvements in fluency, confidence, argumentation and awareness of audience.